MicroRNA-142-3p improves vascular relaxation in uremia. (January 2019) - Kétszeri, Máté; Kirsch, Andrijana; Frauscher, Bianca; Moschovaki-Filippidou, Foteini; Mooslechner, Agnes A.; Kirsch, Alexander H.; Schabhuettl, Corinna; Aringer, Ida; Artinger, Katharina; Pregartner, Gudrun; Ekart, Robert; Breznik, Silva; et al.
Abstract: Background and aims: Chronic kidney disease (CKD) is strongly associated with a high burden of cardiovascular morbidity and mortality. Therefore, we aimed to characterize the putative role of microRNAs (miR)s in uremic vascular remodelling and endothelial dysfunction. Methods: We investigated the expression pattern of miRs in two independent end-stage renal disease (ESRD) cohorts and in the animal model of uremic DBA/2 mice via quantitative RT-PCR. Moreover, DBA/2 mice were treated with intravenous injections of synthetic miR-142-3p mimic and were analysed for functional and morphological vascular changes by mass spectrometry and wire myography. Results: The expression pattern of miRs was regulated in ESRD patients and was reversible after kidney transplantation. Out of tested miRs, only blood miR-142-3p was negatively associated with carotid-femoral pulse-wave velocity in CKD 5D patients. We validated these findings in a murine uremic model and found similar suppression of miR-142-3p as well as decreased acetylcholine-mediated vascular relaxation of the aorta. Therefore, we designed experiments to restore bioavailability of aortic miR-142-3p in vivo via intravenous injection of synthetic miR-142-3p mimic. This intervention restored acetylcholine-mediated vascular relaxation. Conclusions: Taken together, we provide compelling evidence, both in humans and in mice, that miR-142-3p constitutes a potential pharmacological agent to prevent endothelial dysfunction and increased arterial stiffness in ESRD. Graphical abstract: Highlights: Blood miR-142-3p is associated with pulse-wave velocity in uremic patients. miR-142-3p was associated with decreased vascular relaxation in uremic mice. Injection of miR-142-3p mimic restored acetylcholine-mediated aortic relaxation. miR-142-3p might prevent endothelial dysfunction and arterial stiffness in uremia.